Peningkatan Kemampuan Berbahasa Anak dalam Mengemukakan Pendapat melalui Metode Bermain Peran pada Kelompok A TK English School - indasah (Institut Agama Islam Pangeran Diponegoro Nganjuk, 2026)
aspect that enables children to communicate, express ideas, and interact effectively with others. Early childhood represents a critical period for language development, as children begin to build social relationships and acquire communication skills. However, variations in language proficiency among children may occur due to differences in learning experiences and classroom conditions. This study aims to examine the effectiveness of the role-playing method in developing expressive language skills, particularly children’s ability to express opinions and communicate ideas. The research employed a Classroom Action Research (CAR) design involving children in Group A at Rendhawa English School during the 2023–2024 academic year. Data were collected through systematic observations and documentation of children's learning activities. Quantitative analysis was used to determine the percentage of developmental achievement in each cycle, while qualitative analysis was conducted to assess children’s progress based on four developmental categories: not yet developed, beginning to develop, developing as expected, and developing very well. The findings indicate that the implementation of role-playing activities significantly improved children’s expressive language abilities. Through role-playing, children became more confident in expressing opinions, communicating with peers, and participating actively in learning activities. In addition, role-playing provided meaningful social interaction experiences that supported both language development and social competence. Therefore, the role-playing method can be considered an effective instructional strategy for fostering expressive language skills among early childhood learners. Keywords: Expressive Language Skills, Role-Playing Method, Early Childhood Education, Language Development, Classroom Action Research.